"I wonder if I did not mess up….": Shame and resistance among women with epilepsy in Cape Town, South Africa. (October 2018) - Keikelame, Mpoe Johannah; Swartz, Leslie
Highlights: Shame can affect the quality of life of women who have epilepsy. Women with epilepsy may have the power to fight discrimination and injustice. Women with epilepsy can devise strategies to resist abuse and neglect. Bullied victims sometimes use violence to resist victimization and isolation. Multiple factors may predispose women with epilepsy to shame and guilt. Abstract: Purpose: Literature shows that there has been more attention paid to epilepsy stigma, with less focus on issues of shame and resistance. This article provides an in-depth understanding of processes of shame and resistance strategies which emerged from the analysis of individual stories of four adult Xhosa -speaking women with epilepsy in an urban Black township in Cape Town, South Africa. Methods: Our data collection method involved individual in-depth face to face interviews using a semi-structured interview guide adapted from Kleinman's Explanatory Model Framework. This framework enabled participants to openly share their experiences and perspectives of living with the illness. Their audio-recorded qualitative interview data were transcribed and analysed using a thematic data analysis method. Results: Two main themes about processes of shame and resistance strategies emerged. Two women stories provided insights about the different types of emotions related to shame such as feelings of anger, guilt, regret and grief. Resistance strategies against actions of discrimination, unfair treatment and abuse were evident from the stories of the other two women with epilepsy. Being a bully was another form of violent strategy to fight victimization. Conclusion: The findings demonstrate a need for a closer examination of these issues in future epilepsy studies in the study setting – and these should also be examined among men with epilepsy.